Southwest Research-Extension Center, Field Day 1992 (Kansas Agricultural Experiment Station Research Reports, 1992)
Report of agricultural research from Southwest Research-Extension Center of Kansas State University.
Keywords: 1992; SRP657; crops; tillage; irrigation; insect control; weed science